2014
DOI: 10.7120/09627286.23.4.467
|View full text |Cite
|
Sign up to set email alerts
|

The major welfare problems of dairy cows in French commercial farms: an epidemiological approach

Abstract: Animal welfare enhancement requires that problems are reliably identified and ranked in order to prioritise corrective actions. Welfare problems vary with the conditions in which animals are maintained. The objectives were to highlight major welfare problems for dairy cows on farms in France, and find out how farm characteristics (housing and milking systems, breed) could impact specific welfare aspects on these farms. We conducted a cross-sectional survey on 131 French dairy farms. We used the Welfare Quality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
1
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 28 publications
3
12
1
6
Order By: Relevance
“…It should be noted that our FS treatment group showed higher integument alteration rates than those reported elsewhere [29], especially in the tarsus region. The freestalls in our study were smaller than those indicated in current recommendations for adult cows [30].…”
Section: Integument Alterationscontrasting
confidence: 46%
“…It should be noted that our FS treatment group showed higher integument alteration rates than those reported elsewhere [29], especially in the tarsus region. The freestalls in our study were smaller than those indicated in current recommendations for adult cows [30].…”
Section: Integument Alterationscontrasting
confidence: 46%
“…Herd size ranged from 21 to 120 dairy cows of Montbéliarde (French dual-purpose breed) or Holstein breeds. Details on sampling of farms can be found in de Boyer des Roches et al (2014Roches et al ( , 2016. Each farm was visited once.…”
Section: Farms Surveyedmentioning
confidence: 99%
“…To date a large proportion of cattle is disbudded or dehorned, and in most cases without proper pain relief (Fulwider et al, 2008;Vasseur et al, 2010;De Boyer des Roches et al, 2014;Cozzi et al, 2015). A higher percentage of cattle in loose housing systems compared to tie-stall systems are dehorned (Cozzi et al, 2015).…”
Section: Introductionmentioning
confidence: 98%